Latinska epigrafija otoka Krka od IX. do XII. stoljeća. Prilog kontekstualizaciji novopronađenog natpisa u gradu Krku - Matijević-Sokol, Mirjana (2011)
U radu se donosi oris predromaničke epigrafske baštine pisane latinskim jezikom na otoku Krku te posebno obrađuje skupina natpisa XII. st. iz grada Krka povezana s djelatnošću utjecajnih javnih osoba toga vremena. Naglasak je stavljen na nedavno otkriven natpis koji pripada iz dokumenata poznatoj crkvi sv. Ivana iz XII. st. Donosi se potpunija restitucija njegova teksta te se sagledava u kontekstu cjelokupnog korpusa hrvatske latinske epigrafske baštine. Na temelju natpisa i diplomatičke građe krčki primjer potvrđuje pretpostavku da se posvetni natpisi s više naslovnika dotične crkve »otkrivaju« kao obiteljske zadužbine.
This paper describes the pre-Romanesque epigraphic heritage written in Latin on the island of Krk, and particularly refers to the group of inscriptions from the town of Krk, connected to the activity of influential public personae from that time. Particular attention has been paid to the recently discovered inscription belonging to the well-known Saint John’s church from the 12 century in the town of Krk. The paper offers a more complete restitution of the text which is then placed in the context of the entire corpus of Croatian epigraphic heritage. Conclusions drawn from the inscriptions and addressees in epigraphs, as well as diplomatic data from Krk confirm that the inscriptions on churches that list several addressees point to the fact that it marks endowments of noble families. The authors have been taking into consideration all such churches from the early Middle Ages, i.e. from 9th to 12th or 13th centuries, for which there was any kind of epigraphic and/or diplomatic data. A large number of these family endowments have been recorded, both in towns and in the country. Research focused at certain towns for which there was more epigraphic or diplomatic data, and for their hinterland, discovered by archaeological research. Apart from the endowment of the family of Krk bishop Ivan, we have evidenced considerable number of such endowments in Zadar, Split and Bribir county. The results of our analysis allowed us to recognize the endowment of this particular noble family, among seven other addressees in the church near Bribir. It also serves as a paradigm for future research and interpretations.
Projekt MZOS
Projekt MZOS
HRV